Taking sides : clashing views on controversial issues in American history - edited by Larry Madaras and James M. Sorelle (Quilford, CT : Dushkin Pub. Group, 1991)
Contents: v. 1 The colonial period to Reconstruction . - -v. 2 Reconstruction to the present.
Keywords: United States -- History; United States -- Historiography